Impact of stenting on coronary angioplasty procedures. Issue 5 (1st November 1998) - Lee, H S; Densem, C; Levy, R D; Bennett, D H; Ray, S G; Brooks, N H
Abstract : Objective: To compare patient selection and outcome of coronary angioplasty procedures before and after the widespread availability and use of stents. Subjects and methods: Group 1 consisted of 252 consecutive patients and group 2 comprised 389 patients who underwent angioplasty between April 1993 and March 1994, and April 1995 and March 1996, respectively, in a tertiary cardiothoracic centre. Clinical variables were collected before the procedures. Endpoints included in-hospital death, the need for repeat coronary angiography, repeat angioplasty, and coronary artery bypass surgery. Lesions were classified under American Heart Association/American College of Cardiology criteria in 100 randomly selected patients from each group. Results: 311 and 482 angioplasty procedures were performed in patients from groups 1 and 2, respectively. One or more stents were deployed in nine (4%) and 179 (46%, p < 0.01) patients, respectively. The success rate was higher in group 2 than in group 1 patients (483/523 (92%) v 274/372 (88%), respectively, p < 0.05). There were significantly more single vessel angioplasty procedures (198/252 (79%) v 272/389 (70%), p < 0.05), type A lesions (30/116 (26%) v 19/130 (15%), p < 0.05), patients with stable angina (220/252 (87%) v 311/389 (80%), p < 0.05), and fewer acute myocardial infarction patients (1/252 (0%) v 12/389 (3%), p < 0.05) treated in group 1 than in group 2, respectively. Similar numbers of angioplasty were performed in the left anterior descending, left circumflex, and right coronary arteries. There were no significant differences in the in-hospital mortality or the need for repeat coronary angiography, angioplasty, or bypass surgery at 24 hours or six months after the initial procedure. Conclusion: Patients undergoing angioplasty in the stenting era had features associated with an increased risk of complication. Despite this, the primary success rate was higher, and the complication rate and the need for subsequent revascularisation were similar in the two groups, supporting the widely held clinical impression that stenting has made a valuable impact on the practice of angioplasty.